Herpetofauna diversity in northern region of Veracruz, Mexico - Pech Canché, Juan Manuel; Torres-Sebastian, Mario; Chamorro-Florescano, Ivette Alicia (Ecosistemas y Recursos Agropecuarios, 2025)
Amphibians and reptiles (herpetofauna) are an important biological group in ecosystems and also present a great species richness in Veracruz state, however, most of the studies had been focus on the central and southern areas, which creates an information gap in the northern region of the state, therefore, our objective was to analyze the diversity of herpetofauna in three sites in the northern region of the state of Veracruz. Between March and June 2017, the diversity of herpetofauna was analyzed in three sites in the northern region of Veracruz (Tamiahua, Ixhuatlán de Madero and Otontepec) through monthly visits, including within each site three habitats with characteristics that benefit the presence of amphibians and reptiles (e.g. as bodies of water, vegetation cover and areas with agricultural land use). A total of 22 species were recorded, 10 amphibians and 12 reptiles, with Otontepec being the site with the highest alpha diversity of order q and the highest beta diversity associated with turnover, which may be due to the greatest environmental heterogeneity. Six species included in NOM-059-SEMARNAT-2010 were found, one amphibian (Rana berlandieri) and five reptiles (Leptodeira annulata, Leptophis mexicanus, Masticophis mentovarius, Ctenosura acanthura and Dermatemys mawii), which shows the importance of the northern region of Veracruz for the maintenance of herpetofauna diversity and the record of species in some conservation category.
Keywords: Amphibians; beta diversity; turnover; reptils; Veracruz